2007
DOI: 10.1086/522549
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Access to Treatment for HIV Infection

Abstract: The recent recommendations of the Centers for Disease Control and Prevention for opt-out testing are intended to address the evolving human immunodeficiency virus (HIV) epidemic in the United States by bringing more HIV-infected individuals into medical care. This is an important step to better control the epidemic but brings with it the challenges of adequately caring for more individuals infected with HIV and of funding medications and medical care for these additional patients. With more patients being offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The development of personal providers and multidisciplinary care teams are crucial elements of the RWP model of care. One study demonstrated that a successful multi-disciplinary HIV care team needed to include an HIV specialty provider, care coordinator, medication support staff, benefits and insurance coordinator, social worker, and services such as behavioral health support and health education (Cheever, Lubinski, Horberg, & Steinberg, 2007). This team-based model has gained favor for effective management of HIV and other chronic diseases (Rodriguez, Marsden, Landon, Wilson, & Cleary, 2008) and is a core feature of medical homes.…”
Section: Introductionmentioning
confidence: 99%
“…The development of personal providers and multidisciplinary care teams are crucial elements of the RWP model of care. One study demonstrated that a successful multi-disciplinary HIV care team needed to include an HIV specialty provider, care coordinator, medication support staff, benefits and insurance coordinator, social worker, and services such as behavioral health support and health education (Cheever, Lubinski, Horberg, & Steinberg, 2007). This team-based model has gained favor for effective management of HIV and other chronic diseases (Rodriguez, Marsden, Landon, Wilson, & Cleary, 2008) and is a core feature of medical homes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous measures—receiving results from a rapid test, having initial blood work conducted, full intake at a clinic, and actually meeting with a physician at a clinic [911]—have been used to define linkage in research studies. A more expansive view also includes the quality of a successful linkage, having a health care worker’s presence at the post-testing counseling meeting, referral to a multidisciplinary agency that includes both medical and social services, an individualized match between individual and primary care provider, expedited care provided for substance abuse and psychiatric problems and frequent appointment reminders [11].…”
Section: Hiv/aids Continuum Of Carementioning
confidence: 99%
“…Although more private insurers are covering routine HIV testing, very few Medicaid programs have adopted coverage, 15 and uninsured patients would have to pay for the test themselves. The resulting uncertainty about reimbursement for testing is a major barrier that should be addressed.…”
Section: Feasibilitymentioning
confidence: 99%